(3GdMGhj TQM eNJUQ GdeRfjs - (3GdeRfj , ESeGYjd Hf jMji Hf ESeGYjd, CHh EHQGgje,J (B264 (3g` s ((3GHQGgje Hf CHj GdbGSe GdeQYTi s)
(3ChdgG (B:s
(3jHJOF HcJGH GdLfGFR s
(3BNQgG (B:s
(3hjfJgi BNQ cJGH GdML s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B299s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B300 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs